The education of Blacks in the South, 1860-1935 - Anderson, James D., 1944- (The University of North Carolina Press, 1988)
"James Anderson critically reinterprets the history of southern black education from Reconstruction to the Great Depression. By placing black schooling within a political, cultural, and economic context, he offers fresh insights into black commitment to education, the peculiar significance of Tuskegee Institute, and the conflicting goals of various philanthropic groups. Initially, ex-slaves attempted to create an educational system that would support and extend their emancipation, but their children were pushed into a system of industrial education that presupposed black political and economic subordination. This conception of education and social order conflicted with the aspirations of ex-slaves and their descendants, resulting at the turn of the century in a bitter national debate over the purposes of black education. Because blacks lacked economic and political power, white elites were able to control the structure and content of black education during the first third of the twentieth century. Nonetheless, blacks persisted in their struggle to develop an educational system in accordance with their own needs and desires." --